Methodology of training members of river units on a ship simulator - Radojević, Slobodan M.; Kresojević, Milan M.; Šoškić, Svetislav D.; Mihajlović, Dejan D. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/aim: This paper aims to present the methodology for creating educational content/scenarios on a ship simulator (bridge simulator) that will serve officers of river units in developing the ability to react when performing regular and military tactical tasks on the ships of the River Flotilla. Also, training on the simulator aims to train officers of river units using modern information technologies. Methods: The paper uses simulation methods, experimental methods, case studies, and operational research. Results: Specific educational content/scenarios were created, also specific methodology was developed and the principles were clearly defined according to which content/scenarios are created on the ship simulator. Conclusion: By using the ship simulator, in different teaching scenarios, cadets of river units as well as members of river units are trained and acquire the ability to react adequately in real situations in the shortest possible time.